Material characterisation, testing, and modelling of finite element analysis of impact structures - Nichols, Rachel (Cranfield University, 2012)
Formula One race cars have to pass rigorous safety tests before they are allowed on track. This type of testing has been in place for years but the requirements for testing are continually increasing in order to reduce the amount of risk to the drivers’ safety during a race. The number of structures that need to be made and tested can quickly make this process an expensive one. Additionally, it is necessary to pass the mandated tests within a reasonable amount of time so as not to have an impact on the development on the rest of the car. There is a desire to reduce the number of structures needed for testing through finite element analysis (FEA), and as such, to reduce the time needed to pass the safety tests. FEA of laminated composites can be complex and is a balance between accuracy and the time it takes to find a solution. The current project looks into increasing understanding of the requirements for material characterisation, experimental impact testing, and explicit simulation of a carbon fibre fabric pre-impregnated with epoxy resin. Mercedes-Benz Grand Prix (MGP) Formula One Team has provided a pre-preg material for evaluation. Material experiments were performed per the American Society for Materials and Testing (ASTM) in order to find the tensile modulus, tensile strength, Poisson’s ratio, compressive strength, shear modulus, and shear strength of the material. Nine tubes were manufactured at MGP and tested in the drop tower at the Cranfield Impact Centre (CIC) ... [cont.].
Keywords: Formula One; material model validation; LS-DYNA